18F-Sodium Fluoride PET/CT in Oncology: An Atlas of SUVs. (April 2015) - Sabbah, Nathanael; Jackson, Tatianie; Mosci, Camila; Jamali, Mehran; Minamimoto, Ryogo; Quon, Andrew; Mittra, Erik S.; Iagaru, Andrei
Abstract : Purpose: The purpose of this study was to analyze the distribution of 18 F Sodium Fluoride ( 18 F-NaF) uptake in the normal skeleton, benign and malignant bone lesions, and extraskeletal tissues, using semiquantitative SUV measurements. Patients and Methods: We retrospectively analyzed data from 129 patients who had 18 F-NaF PET/CT at our institution for an oncological diagnosis between 2007 and 2014. There were 99 men and 30 women, 19 to 90 years old (mean [SD], 61.5 [15.5]). The range, average, and SD of SUV were measured for normal bone and extraskeletal tissues uptake for the entire patient population. A separate statistical analysis was performed to compare group A, which corresponds to the population of patient with no 18 F-NaF–avid metastatic lesions, and group B, which corresponds to the population of patient with 18 F-NaF–avid metastatic lesions. We also measured SUVmax and SUVmean for bony metastases and degenerative changes Results: The PET/CT images were acquired at 30 to 169 minutes (mean [SD], 76.5 [22.8]) after injection of 3.9 to 13.6 mCi (mean [SD], 7.3 [2.4]) of 18 F-NaF. The range and mean (SD) of SUVmax for 18 F-NaF–avid metastasis were 4.5 to 103.3 and 25.9 (16.6) and for 18 F-NaF–avid degenerative changes were 3.3 to 52.1 and 16.5 (7.9), respectively. Conclusions: Various skeletal sites have different normal SUVs. Skeletal metastases have different SUVs when compared with benign findings such as degenerative changes.